Aliens in the promised land : why minority leadership is overlooked in white Christian churches and institutions - Bradley, Anthony B. (Phillipsburg, P&R Publishing, 2013)
"In an age when church growth is centered in Africa, Asia, and Latin America, evangelicalism must adapt to changing demographics or risk becoming irrelevant. Yet many evangelicals behave 'tribally'-valuing the perspective of only those like themselves-while also denying any evidence of racial attitudes in the church. Anthony Bradley has gathered scholars and leaders from diverse 'tribes'-black, Hispanic, and Asian-to share advice on building relationships with minority denominations and valuing the perspectives and leadership of minority Christians (not just their token presence.) They seek to help evangelicalism more faithfully show the world that the gospel brings together in Christ people from all tribes, languages, and cultures"--Publisher description.
General introduction : my story / Anthony B. Bradley -- Black pastoral leadership and church planting / Lance Lewis -- Race and racialization in a post-racist evangelicalism : a view from Asian America / Amos Yong -- Serving alongside Latinos in a multiethnic, transnational, rapidly changing world
Includes bibliographical references (pages 213-243) and index.
Keywords: Christian leadership; Church and minorities; Diversity in the workplace